Strength of Finnish grown timber - Ranta-Maunus, Alpo (VTT Technical Research Centre of Finland, 2007)
Strength and stiffness of timber have been studied in different projects during 1986-2007. This is a summary report of results which are considered relevant for European and international standardisation. It includes both new unpublished and already published information. The growth area of timber considered in this publication is primarily limited to Finland and parts of North Western Russia. This experimental research concerns bending, tension, compression and shear strength and stiffness of sawn timber. It includes also tension perpendicular to grain of glulam and compression perpendicular to grain of sawn timber. Also, bending and compression strength of round timber is reported. In addition, long term creep results of glulam and other structural wood products are included in this publication.